A technology development framework for scenario planning and futures studies using causal modeling. Issue 8 (3rd August 2022) - Tavana, Madjid; Ghasrikhouzani, Mohsen; Abtahi, Amir-Reza
ABSTRACT: Planning for the future plays a pivotal role in a competitive business world. Scenario analysis is a popular tool for exploring plausible futures and planning. However, the practice of scenario planning is often qualitative, unstructured, and time-consuming. We propose a structured technology development framework by categorising the qualitative variables impacting technology development and identifying their causal relationships. We then use causal loops and expert opinions and the Decision Making Trial and Evaluation Laboratory (DEMATEL) method for scenario planning and futures studies. We present a case study in the communications industry to demonstrate the applicability of the proposed framework.